Effect of tree-ring detrending method on apparent growth trends of black and white spruce in interior Alaska. (31st October 2016) - Sullivan, Patrick F; Pattison, Robert R; Brownlee, Annalis H; Cahoon, Sean M P; Hollingsworth, Teresa N
Abstract: Boreal forests are critical sinks in the global carbon cycle. However, recent studies have revealed increasing frequency and extent of wildfires, decreasing landscape greenness, increasing tree mortality and declining growth of black and white spruce in boreal North America. We measured ring widths from a large set of increment cores collected across a vast area of interior Alaska and examined implications of data processing decisions for apparent trends in black and white spruce growth. We found that choice of detrending method had important implications for apparent long-term growth trends and the strength of climate-growth correlations. Trends varied from strong increases in growth since the Industrial Revolution, when ring widths were detrended using single-curve regional curve standardization (RCS), to strong decreases in growth, when ring widths were normalized by fitting a horizontal line to each ring width series. All methods revealed a pronounced growth peak for black and white spruce centered near 1940. Most detrending methods showed a decline from the peak, leaving recent growth of both species near the long-term mean. Climate-growth analyses revealed negative correlations with growing season temperature and positive correlations with August precipitation for both species. Multiple-curve RCS detrending produced the strongest and/or greatest number of significant climate-growth correlations. Results provide important historical context for recent growth of black and white spruce. Growth of both species might decline with future warming, if not mitigated by increasing precipitation. However, widespread drought-induced mortality is probably not imminent, given that recent growth was near the long-term mean.